Perception of Quality in a Philippine Private Academic Institution (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2020)
The purpose of this research is to obtain information and measure the service quality experience in a Philippine Private Academic Institution. This study used quantitative descriptive research method utilizing individual level data through adapted research instrument from Pamatmat et. al. (2018) utilizing the Service Quality Dimension. Percentage, Mean Score, Frequency Distribution, T-test and ANOVA were used for data analysis. The study sought the participation of 290 parents from a private academic institution in North Metro Manila. Using snowball sampling method, the 290 parents’ respondents were derived using the Slovin’sformula based form the total student population of 1,061 admitted during school year 2018-2019 from the private institution. The Service Quality Experience Instrument was found to be highly reliable (38 items; α = .873). The result highlights the five dimensions of service quality experience where Place of resident and civil status was significant with the five dimension of service quality. Sex was significant to responsiveness. Educational Attainment was significant to assurance. Monthly Income was significant to assurance, empathy, reliability, and responsiveness. Sex was significant to assurance, reliability and responsiveness. Tangible scored lowest possibly due to the concern on parking space availability which might have impact the totality of the raw score for the tangible service quality dimension.  Assurance scored the highest wherein the item that got the highest score was pertaining to the community involvement of the private academic institution.